267 Twenty years of pfd non-wearing and wearing among child and youth boating immersion victims in Canada. (1st September 2016) - Barss, Peter; Olsen, Karlyn; Hamilton, Jane; Dalke, Shelley
Abstract : Background: Boating is the most frequent activity for water-related immersion deaths in Canada. Central in immersion/drowning is non-wearing of personal flotation devices (PFDs). Although most boating victims are adult males, wearing and compliance with regulations was assessed for children 0–14-years-old and youth 15–19 victims of immersion deaths. Indigenous were compared with other ethnicities. Methods: Annual Red Cross collection of 1991-2010 Canadian coroner data by structured questionnaire. Analysis included activity, purpose, personal, equipment, environment factors. Results: Among 2678 recreational and daily living boating victims during 1991–2010, included were infants less than 1 year old 4, toddlers 1–4 years old 18, 5–14 year olds 57 and youth 15–19 years old 219. By sex, all 4 infants were male, 13 toddlers male and 5 female, 40 of 5–14s male and 17 female, and 198 youth male and 21 female. 20% of 0–14-year-old victims were properly wearing a PFD, compared with 11% for youth 15–19 years. For 35% of child boaters, there was reportedly no PFD present, representing a violation of current legislation, and for another 27% it was unknown whether a PFD was present. Hence as many as 62% were in violation. For indigenous children, in 63% no PFD was present, and for 17% unknown, i.e., as high as 80s in violation, compared with other ethnicities where 21% were not present and 26% unknown. Concerning youth, for 40% no PFD was present, and for 28% unknown, hence as high as 68% in violation. Among indigenous youth, 58% had no PFD present and 36% unknown, i.?e., as high as 92% in violation. For other ethnicities, 41% had no PFD present and 26% unknown. 33% of 0–14-year-old non-indigenous victims were properly wearing a PFD, and 13% of 15–?19-?year-olds. Not a single aboriginal victim 0–19 years was properly wearing a PFD during the 20 year period, compared with 18% for other ethnicities. 25% of victims 0–14 years were alone or with minors only. For the remaining 75%, at least one adult was present. For 15–19-year-olds, 20% were alone or with minors only, 65% with at least one adult and 13% with others. Of the 17 victims 0–19 years alone at the time of the incident, only one was wearing a PFD. For 0–14 year olds with an adult, 25% were properly wearing a PFD, and for 15–19 year olds, 13%. Conclusions: Wearing of a flotation device was low among all child and youth immersion victims. Non-wearing was markedly lower among indigenous victims. Special effort is needed to address non-wearing and lack of compliance with regulations among indigenous peoples of Canada.